Schopenhauer’s Irrationalism and the Crisis of German Classical Idealism - Andrijauskas, Antanas (Problemos, 1982)
The German classical idealism and its meditative method of world cognition was found to be unable to interpret the aggregate of the new crisis processes that deeply moved the foundation of bourgeois society and of its derivative -the consciousness. Making use of the intensified crisis in rationalism and seizing the opportunity of the constantly rising topicality of the human personality problem, the irrationalism represented by A. Schopenhauer was striving not only at striking a crippling blow to Hegelian panlogism, historism, but also at establishing the primacy of irrational “will” interpreted as a substantial, allpenetrating origin of the world. It is in Schopenhauer’s philosophy that one can notice an attraction towards a synthesis of philosophical and art thought, towards aesthetization and ontologization of philosophical problems. The tendency of this kind reflected the incapability of an ontologically orientated philosophy in answering the urgent questions and thus symbolized its escape from real contradictions to the realm of subjectivism.